2015
DOI: 10.3390/molecules200813620
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Analysis of Various Date Palm Fruit (Phoenix dactylifera L.) Cultivars from Saudi Arabia to Assess Their Nutritional Quality

Abstract: Date palm is an important crop, especially in the hot-arid regions of the world. Date palm fruits have high nutritional and therapeutic value and possess significant antibacterial and antifungal properties. In this study, we performed bioactivity analyses and metabolic profiling of date fruits of 12 cultivars from Saudi Arabia to assess their nutritional value. Our results showed that the date extracts from different cultivars have different free radical OPEN ACCESSMolecules 2015, 20 13621 scavenging and anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
178
4
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(199 citation statements)
references
References 59 publications
6
178
4
11
Order By: Relevance
“…These results showed that the rutin and kaempferol were identified in all Chamaerops extracts, a higher content was obtained in methanol extracts of leaflets (33 ± 2 µg g -1 ), water was extracted three times less rutin LW (10.9 ± 0.54 µg g -1 ). On a previous study rutin was identified from the C. humilis leaves (Hirai et al, 1986) and Phoenix dactylifera L. fruits (Hamad et al, 2015).…”
Section: Most Of the Compounds In Ms Exhibited Abundant [M -H] In Negmentioning
confidence: 95%
“…These results showed that the rutin and kaempferol were identified in all Chamaerops extracts, a higher content was obtained in methanol extracts of leaflets (33 ± 2 µg g -1 ), water was extracted three times less rutin LW (10.9 ± 0.54 µg g -1 ). On a previous study rutin was identified from the C. humilis leaves (Hirai et al, 1986) and Phoenix dactylifera L. fruits (Hamad et al, 2015).…”
Section: Most Of the Compounds In Ms Exhibited Abundant [M -H] In Negmentioning
confidence: 95%
“…The existence of a genetic map (Mathew et al, 2014) makes it possible to choose useful genes, clone them and transform them into date palms to increase the yield or to improve agronomic qualities. Targeted genetic improvement programs will allow increasing the quantitative and specific secondary metabolites (Hamad et al, 2015) in planta. The in vitro culture of date palm is well establi-shed, and shoot tips are primarily used as explants for micropropagation.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic profiling of different varieties of date palm revealed varying level of chemical ingredients such as phenolics, amino acids and minerals. Efficacies of various biological activities have also been reported to be dependent upon the type of cultivars and on the ripening stage of fruits (Amira et al 2012;Hamad et al 2015). Al-Dous et al (2011) identified 32 SNP (in total 3.5 million) in the genomes of the three date palm varieties.…”
Section: Comparative Genomicsmentioning
confidence: 99%